The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0269215508101749
|View full text |Cite
|
Sign up to set email alerts
|

Changing self-efficacy in individuals following a first time stroke: preliminary study of a novel self-management intervention

Abstract: There is preliminary evidence that the use of an individualized stroke self-management intervention is acceptable and can lead to a change in self-efficacy in this small sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 28 publications
2
115
0
2
Order By: Relevance
“…There has been a substantial increase in the body of literature to suggest the effects of self-management interventions on rehabilitation and recovery across a variety of chronic conditions such as stroke (Jones et al, 2009), lymphoedema (McGowan et al, 2013), chronic obstructive pulmonary disease (Fairbrother et al, 2013;Bourbeau et al, 2013) and vascular risk reduction (Sol et al, 2005;Sol et al, 2008;Mead et al, 2010;Maitland and Chalmers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a substantial increase in the body of literature to suggest the effects of self-management interventions on rehabilitation and recovery across a variety of chronic conditions such as stroke (Jones et al, 2009), lymphoedema (McGowan et al, 2013), chronic obstructive pulmonary disease (Fairbrother et al, 2013;Bourbeau et al, 2013) and vascular risk reduction (Sol et al, 2005;Sol et al, 2008;Mead et al, 2010;Maitland and Chalmers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the actions included in advise, we highlight health education, especially aimed at patient's self-management of their chronic condition (38) , being associated with better clinical outcomes and lower costs (36) . This strategy must be supported by scientific evidence and clinical guidelines (31,(33)(34) to promote behavior change in a more extensive and permanent way.…”
Section: Discussionmentioning
confidence: 99%
“…Establish an intervention program with weekly sessions with the aim of improving the knowledge of patients and involve them in selfmanagement (12,18,29,(35)(36)(37) , including the use of educational booklets about self-management (38) *.…”
Section: Advisementioning
confidence: 99%
“…The Bridges selfmanagement programme began in stroke but has now extended to brain injury and other complex neurological conditions and in acute and community healthcare settings (Jones, Mandy, & Partridge, 2009;Makela, 2015). Social cognition theory has underpinned our work and self-efficacy was a critical first construct within Bridges (Bandura, 1997).…”
Section: History Of Bridgesmentioning
confidence: 99%
“…Research to develop and test the Bridges stroke self-management programme has shown proof of concept, efficacy, acceptability and feasibility as an approach integrated into rehabilitation (Jones et al, 2009(Jones et al, , 2016McKenna et al, 2013). But we are now mindful that evidence in a trial setting does not help us understand how rehabilitation teams and professionals integrate and sustain self-management support which preferences needs, goals and skills of individuals.…”
Section: History Of Bridgesmentioning
confidence: 99%